The politics of mourning: The virtual memorialisation of British fatalities in Iraq and Afghanistan. (July 2015) - Danilova, Nataliya
This article analyses the virtual memorialisation of British fatalities in Iraq and Afghanistan. It will study online obituaries published on two websites – BBC news and The Lasting Tribute. These sources are compared as examples of media-driven and community-driven memorialisation. This comparison enables us to study links between the mainstream media and the functioning of digital network communities, between public and private discourses of war memorialisation. The purpose of analysis is twofold: first, the article examines how virtual memorials represent fatalities, and, second, it discusses the political implications of virtual memorialisation. The article posits that although virtual memorials introduce professionalised and personalised accounts of the deaths of service personnel, they also enable a nationalistic discourse of war commemoration, and shape the politics of mourning in modern Britain.